Modern methods of treatment of precancerous vulvar diseases, with a focus on photodynamic therapy: literature review - N. A. Shanazarov; S. V. Zinchenko; S. D. Kisikova; M. A. Alchimbayeva; K. S. Seitbekova; I. Z. Galiev; M. M. Ibragim (Южно-Российский онкологический журнал)
Precancerous diseases of the vulva, such as dysplasia and leukoplakia and lichen sclerosus, are a significant problem in gynecology, since their progression can lead to the development of invasive cancer, which endangers the health and life of women. Modern treatment methods, including surgery and topical medications, do not always provide adequate effectiveness, which underscores the importance of finding alternative approaches. Photodynamic therapy (PDT), which is an innovative method, shows promising results in the treatment of precancerous and early tumor diseases, including those affecting the mucous membranes of the vulva. This method, acting on pathological cells with the help of photosensitive drugs and light, minimizes damage to healthy tissues, which makes it promising in clinical practice. The novelty of this study lies in the systematic analysis of the use of PDT specifically for the treatment of precancerous diseases of the vulva, which is still poorly understood.Purpose of the study. To study the effectiveness of various methods of treating precancerous diseases of the vulva, with a focus on photodynamic therapy (via literature review).Materials and methods. A literature search for studies published over the past 5 years was conducted in the Pubmed, Google Scholar, ClinicalTrial.gov, The Cochrane Library, NICE, eLIBRARY and CyberLeninka databases in English and Russian. Global statistical data on tumors of the female genital organs were also studied, especially in the Russian Federation and the Republic of Kazakhstan. As a result of a search query, 5,369 articles were submitted to the above databases. In total, this review examines 50 scientific articles exploring various methods of treating precancerous diseases of the vulva.Results. The results of the study showed that various treatments for precancerous vulvar diseases, including surgical and drug approaches, have limited effectiveness and may be accompanied by side effects such as scarring or recurrence. At the same time, photodynamic therapy has demonstrated high clinical efficacy, providing significant improvement in tissue condition with minimal damage to healthy cells. The method has shown good results in reducing pathological changes such as hyperkeratosis and dysplasia, with a low recurrence rate and rapid tissue repair. In addition, PDT has demonstrated good tolerability and safety, which confirms its promise as an effective and minimally invasive method of treating precancerous diseases of the vulva.Conclusion. PDT can provide high efficiency in disease regression and human papillomavirus (HPV) clearance, as well as help reduce the recurrence of precancerous vulvar diseases.